Practical music learning: An investigation into institutional differences between schools and specialist music centres in the Greater Cape Town Area - West, David John (2023)
ENGLISH ABSTRACT: This research set out to investigate the dynamic environment within music departments in academic schools and music centres in relation to practical music learning (PML). The aim was to uncover which aspects affect PML in a positive or negative way, and which of these are generic, or unique to a specific type of institution. Areas explored included facilities, scheduling, teaching space, ensemble programmes, and approaches towards additional activities like examinations, eisteddfods and competitions. A mixed methods approach was employed in order to explore teachers’ perspectives (qualitative data) and students’ perspectives (quantitative data). Qualitative data, collected in the form of interviews and focus group discussions, explored eight instrumental teachers’ teaching philosophies, and their attempts to navigate the dynamic PML environment. Quantitative data was collected though a survey questionnaire, and was used to support or refute qualitative data. Data was analysed and organised to describe features within the learning environment in various different institutions. This data is also contextualised through an initial orientation overview into school systems and music offering of school music departments and music centres. Interviewed teachers prioritise progress, educational value, enjoyment, and a degree of student choice in their teaching philosophies. Some distinctive differences between academic schools were explored, and it became apparent that there is a great degree of variance between music departments in different public academic schools. Participants encountered challenges in scheduling and room allocation, which frequently impacted on teaching time. Although in many situations participants described good music departments and facilities, which was backed up with the quantitative data, the practicality of some teaching spaces for PML was discovered to be inadequate. Reasons for this include available space, acoustics suitable to develop tone production, and rooms that are inappropriate or demeaning for the purposes of PML. Although the availability of ensemble activities was found to be universal, the type of ensemble offering varied between different institutions. Support for external activities like examinations and eisteddfods varied among participants, and support was tempered by student choice. Music teachers are inclined to opt for and remain at music departments or music centres where there is a strong culture of music within the institution and among all the role players: management, other subject teachers, music teachers and parents. Other important features include strong management, good lines of communication and good facilities that meet the requirements for PML. Retaining competent, motivated staff is likely to add to the strength of music departments and music centres, which in turn will have a positive influence on PML.